Influência do método de síntese na estrutura e dimensionalidade de polímeros de coordenação - Rosa, Iara Maria Landre (2016)
Coordination polymers (CPs) are hybrid compounds formed by repetition of monomeric units via covalent bonds. These networks, which are formed basically by metals covalently bonded to organic molecules (ligands) can present structures with one, two and three-dimensional linkage between metal and ligand. In recent decades this material has gained wide attention due to their potential applications in gas storage and absorption, heterogeneous catalysis, nonlinear optics and magnetism. However, control of the synthesis of these compounds is still a challenge, since several factors such as pH, temperature, solvent, counter-ion and synthetic method can influence directly on the obtained product. The present study aims the synthesis, characterization and investigation of the influence of synthetic routes in obtaining new coordination polymers with the first row transition metals (Mn²+, Co²+, Cu²+ and Zn²+) coordinated to the dicarboxylic organic acids (adipic acid, 5-aminoisophtalic acid, 2,5-dihydroxyterephtalic acid, fumaric acid and terephthalic acid). For synthesis, was used the following techniques: conventional method with pH control, diffusion methods, solvothermal method and mechanochemical method. Single crystals were obtained by the diffusion method, which provided novel polymeric products of the following reactions: (i) adipic acid with Co²+ and Zn²+; (ii) 5-aminoisophtalic acid with Mn²+; (iii) 2,5-dihydroxyterephtalic acid with Co²+ and Zn²+; (iv) terephthalic acid with Cu²+ and Mn²+. The CPs obtained here were characterized by vibrational spectroscopy in the infrared (IR), thermal gravimetric analysis (TG), elemental analysis (CHN) and powder (PXRD) and single crystal (SCXRD) X-ray diffraction. Their molecular and supramolecular structures were discussed.